A Pollution of mercury and cyanide soils and plants in surrounding in the Artisanal and Small-Scale Gold Mining (ASGM) at Sekotong District, West Lombok, West Nusa Tenggara - Suhadi Suhadi; Sueb Sueb; B. K. Muliya; Anisa Meilia Ashoffi (Biological Environment and Pollution, 2021)
The Artisanal and small-scale gold mining (ASGM) activities at Sekotong District, NTB have a negative impact on the environment. This study aims to determine the content of mercury and cyanide in soil and plants around gold mining. The research method used is descriptive explorative. The research sample was taken purposively at 4 locations and sample analysis at the Chemical Laboratory of Universitas Brawijaya. The results showed that the Hg and HCN content in surface soil ranged from 2.90-26.94 and 63.93-104.08 mg/Kg, Hg and HCN in soil with a depth of 30 cm ranging from 3.48-53.86 and 66.59-106.55 mg/Kg. The Hg and HCN content in plants ranges from 1.23-8.15 and 18.41-52.85 mg/Kg. Referring to the standards set by WHO and the rules of Health the Republic Indonesia 2016, soil and plants have polluted and have a negative impact on other living things.